Auto-Tuning PI Controller Design Using Fuzzy Logic Controller for Web Tension Control in Roll Rewinder System - Ahmad Faizal; Rahmadeni Rahmadeni; Elfira Safitri; Juliesty Huswina; Rudy Kurniawan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2022)
Paper has a very important role, because it increases the productivity of pulp and paper companies in Indonesia. The company's development in 2018 increased by 2.1%, this was indicated by increasing consumer demand. Therefore, paper becomes a necessity in everyday life. The criteria for the paper to be produced are paper with a flat surface and cannot be wrinkled. However, errors in paper production that often occur are a lot of wrinkles and uneven paper surfaces. This happens because of a discrepancy in the dynamics of paper tension with the standards that have been set. The paper record is caused by the dynamics of the web tension in the Rewinder Roll system. In order for the web tension to remain stable, a controller is needed. The controller used is Auto-Tuning PI controller using Fuzzy Logic Controller (FLC). The controller can be said to be successful when it is able to perform automatic tuning of setpoint changes. The results showed that the system was able to achieve setpoint values, overcome overshoot and steady-state error (Ess) with response time values, namely Tr=0.3151 seconds, Ts=0.3750, Td=0.0721, overshoot=0.0044%, and Ess=0 N.